Several Aspects of Analysis of a Literary Work - Žukas, Saulius (Problemos, 1986)
Attempts to create the scientific theory of analysis of a literary work (J. M. Lotman’s conception) are considered. Attention is paid to the interrelation between the modem structuralistic analysis of a text and the tradition of hermeneutics. The process of understanding is discussed in detail. The hypotheticality of the original structuring of a text and thus the necessity of investigation of the resulting hypotheses is pointed out. The need of new interpretations of classical texts is also discussed.